P178 Traumatic recto-vaginal fistula after consensual sexual activity: a case series. (8th June 2017) - Waite, Kathryn; Webster, Claire; Karandikar, Sharad; Bowley, Doug
Abstract : Introduction: Consensual vaginal intercourse may be associated with relatively minor genital injury, such as mucosal abrasions, tears or ecchymoses. More severe genital injury is more likely to be associated with rape or sexual assault by penetration with an object. Conversely, we know that the absence of genital injury does not mean that rape or serious sexual assault did not occur. Methods: We report a small series of patients presenting with severe and life-threatening genital injury after consensual sexual activity. Results: An adult woman presented with lower abdominal pain and faeculent vaginal discharge after sexual activity with her intimate partner involving consensual and simultaneous insertion of two sex toys (one per rectum and another per vaginam ). She had sustained a 100mm defect in the posterior vaginal and antero-lateral rectal walls. Despite surgery and faecal diversion, she developed severe sepsis that required extended critical care. A second patient presented with faeculent discharge per vaginam after consensual, 'conventional' peno-vaginal intercourse. On examination, she was found to have a 30 × 20 mm low recto-vaginal fistula; on this occasion not associated with peritoneal contamination or serious septic response. Discussion: Traumatic recto-vaginal fistulae are rare with implications for both immediate morbidity and mortality and long-term physical and mental well-being. These cases demonstrate the extreme spectrum of genital injury that may be associated with consensual sexual activity. Recognition that this severity of injury can occur following consensual activity is important and our first patient's story also highlights some of the public health implications concerning the use and regulation of sex toys.